Smuggling and "coastal piracy" in Nigeria : proceeding on a workshop, NIIA/Nigerian Navy, February 22-23, 1983 - Akindele, R. A.; Vogt, Margaret A.; Nigerian Institute of International Affairs; The Nigerian Navy. (Lagos : Nigerian Institute of International Affairs, 1983)
This volume is the proceeding of a workshop on Smuggling and "coastal piracy" in Nigeria by Nigerian Institute of International Affairs, (NIIA) and the Nigerian Navy, February 22-23, 1983 / It examines measure that can use to stop smuggling and coastal piracy in Nigerian water way.
oo 12/04/2019
Loans
Keywords: Smuggling; Coast defenses; Territorial waters; Nigeria